Perlindungan Hukum Terhadap Indikasi Geografis Milik Indonesia Yang Telah Terdaftar Sebagai Merek Oleh Pengusaha Asing - Febriyanti Abdul Kadir; Merry Tjoanda; Theresia Nolda Agnes Narwadan (PATTIMURA Law Study Review, 2023)
ABSTRACT: Legal protection for geographical indications is regulated in TRIPs article 22 paragraph 3 which determines: "A member, ex officio if his legislation permits or at the request of an interested party refuses or cancels the registration of a trademark containing or constituting a geographical indication in relation to goods that are not originating from the area mentioned if the use on behalf of a geographical indication in a trademark for goods misleads the members of the community regarding the actual area of ​​origin.” There are several cases of violations of geographical indications belonging to Indonesia which were registered as trademarks by foreign businessmen, namely the case of Toraja coffee which was registered in Japan as a coffee brand with the name Toarco Toraja by the company Key Coffee Inc Corporation. The second case is the Gayo coffee brand which is claimed to belong to a Holland Coffee company from the Netherlands which is registered at European Coffee Bv under the name Gayo Mountain Coffee. The research method used is normative juridical, using statutory approaches, conceptual approaches. Sources of primary, secondary and tertiary legal materials. The technique of collecting legal materials is library research, journals, internet media, which are analyzed using qualitative methods. The results of the study show that legal protection for geographical indications belonging to Indonesia that have been registered as trademarks by foreign entrepreneurs consists of preventive legal protection in the form of registration of geographical indications to the director general of intellectual property rights, and repressive legal protection in the form of appeals, use of marks that are the same as geographical indications, deletion of indications geographic, civil and criminal law enforcement. Efforts to resolve cases of infringement of geographical indications belonging to Indonesia that have been registered as trademarks by foreign entrepreneurs, can be resolved by means of litigation and also by means of non-litigation.